The effect of sharia financial literacy, trust on the decision to use a digital wallet / Hastuti Olivia, Widia Astuty and Astrid Aulia Farizki - Olivia, Hastuti; Astuty, Widia; Farizki, Astrid Aulia (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The shortage of financial literacy of Shariah in the Z-generation in shariah transactions so that many generations of Z still use non-Shariah digital wallets. This study looked at the influence of Sharia financial literacy, belief in interest in using digital wallet applications on Generation Z The respondents of this study were 160 who were students of the 4th semester of Sharia Accounting School who had received sharia accounting courses. The study uses a quantitative method with the SmartPLS 3.0 test tool. The results of this study did not affect the interests and beliefs of students in using digital wallet applications. The shortage of sharia financial literacy makes still many generations of Z use non-sharia digital wallet applications.